Soybean Cyst Nematode Resistance Emerged via Artificial Selection of Duplicated Serine Hydroxymethyltransferase Genes - Wu, Xiao-Yi; Zhou, Guang-Can; Chen, Yun-Xia; Wu, Ping; Liu, Li-Wei; Ma, Fang-Fang; Wu, Mian; Liu, Cheng-Chen; Zeng, Ying-Jie; Chu, Alexander E.; Hang, Yue-Yu; Chen, Jian-Qun; et al. (Frontiers in Plant Science, 2016)
A major soybean (Forrest cultivar) quantitative trait locus (QTL) gene, Rhg4, which controls resistance to soybean cyst nematodes (SCN), encodes the enzyme serine hydroxylmethyltransferase (SHMT). The resistant allele possesses two critical missense mutations (P130R and N358Y) compared to that of the sensitive allele, rhg4. To understand the evolutionary history of this gene, sequences of 117 SHMT family members from 18 representative plant species were used to reconstruct their phylogeny. According to this phylogeny, the plant SHMT gene family can be divided into two groups and four subgroups (Ia, Ib, IIa and IIb). Belonging to the Subgroup Ia lineage, the rhg4 gene evolved from a recent duplication event in Glycine spp. To further explore how the SCN-resistant allele emerged, both the rhg4 gene and its closest homolog, the rhg4h gene, were isolated from 33 cultivated and 68 wild soybean varieties. The results suggested that after gene duplication, the soybean rhg4 gene accumulated a higher number of nonsynonymous mutations than rhg4h did. Although a higher number of segregating sites and gene haplotypes were detected in wild soybeans than in cultivars, the SCN-resistant Rhg4 allele (represented by haplotype 4) was not found in wild varieties. Instead, a very similar allele, haplotype 3, was observed in wild soybeans at a frequency of 7.4%, although it lacked the two critical nonsynonymous substitutions. Taken together, these findings support that the SCN-resistant Rhg4 allele likely emerged via artificial selection during the soybean domestication process, based on a SCN-sensitive allele inherited from wild soybeans.